2007
DOI: 10.1098/rsif.2007.0217
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic model for infectious salmon anemia (ISA) in Atlantic salmon farming

Abstract: Infectious salmon anemia (ISA) is one of the main infectious diseases in Atlantic salmon farming with major economical implications. Despite the strong regulatory interventions, the ISA epidemic is not under control, worldwide. We study the data covering salmon farming in Norway from 2002 to 2005 and propose a stochastic space-time model for the transmission of the virus. We model seaway transmission between farm sites, transmission through shared management and infrastructure, biomass effects and other potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 25 publications
2
47
1
Order By: Relevance
“…Jarp & Karlsen (1997) identified an enhanced risk of infection (odds ratio 8) if infected farms were within 5 km of the farm assessed, the odds increasing as the distance decreased. Scheel et al (2007) and Lyngstad et al (2008) have also identified proximity as a risk factor.These modes of transport are effective over different distances and result in a variety of patterns of spread. In the present study, the significance of different forms of spread is assessed in the light of the outbreak pattern and data on contact distributions implied by these different routes.…”
mentioning
confidence: 99%
“…Jarp & Karlsen (1997) identified an enhanced risk of infection (odds ratio 8) if infected farms were within 5 km of the farm assessed, the odds increasing as the distance decreased. Scheel et al (2007) and Lyngstad et al (2008) have also identified proximity as a risk factor.These modes of transport are effective over different distances and result in a variety of patterns of spread. In the present study, the significance of different forms of spread is assessed in the light of the outbreak pattern and data on contact distributions implied by these different routes.…”
mentioning
confidence: 99%
“…This comparatively local spread for ISA is in agreement with Jarp and Karlsen (1997), who found that approximately 50 % of ISA cases in Norwegian sea sites were within 10 km of other ISA positive sites. Scheel et al (2007) suggest that the risk for ISA of being in the same local contact network is equal to that due to seaway distance at a distance of 5 km. We use these data to parameterise the transmission kernel.…”
Section: Effect Of the Transmission Kernelmentioning
confidence: 99%
“…From Scheel et al (2007), we assume an effective farm size at the distance where local contact is equivalent to seaway distance: d 0 = 5 km. We then re-express equation (14) into the following form, where φ represents a proportional drop in infectivity due to the distance kernel over the…”
Section: Effect Of the Transmission Kernelmentioning
confidence: 99%
See 2 more Smart Citations